Skrining Bakteri Asam Laktat Dan Khamir Potensial Proteolitik Ekstraseluler Dan Milk Clotting Activity Dari Ekstrak Dan Fresh Cheese Nanas (Ananas comosus (L.) Merr.) - Putri, Agni Annisa; Rustama, Mia Miranti; Putranto, Wendry Setiyadi (Unpad Press, 2023)
Fresh cheese is a dairy product produced from the coagulation process of milk using the rennin enzyme which does not require a ripening process. Extracellular proteolytic enzymes for cheese production can be produced from pineapple (Ananas comosus L. Merr) and microbes, such as Lactic Acid Bacteria (LAB) and yeast. This study aims to obtain Lactic Acid Bacteria (LAB) and yeast which have the potential for extracellular protease and Milk Clotting Activity (MCA) from fresh cheese and pinapple extract. The results showed that the total LAB from fresh cheese using pineapple was 5.6 x 10 5 CFU/g, from pineapple extract was 4.6 x10 5 CFU/ml, and from pasteurized milk was 1.9 x 10 4 CFU/ml. The total yeast from fresh cheese using pineapple was 5.1 x 10 4 CFU/g, from pineapple extract was 4.2 x 10 4 CFU/m and pasteurized milk was 4.0 x 10 3 CFU/ml. In this study found 8 LAB isolates from pineapple extract and fresh cheese had proteolytic activity with a proteolytic index value between 0.17 to 2.14 and had MCA abilities of 24 to 233 SU/ml. 5 yeast isolates from pineapple extract and fresh cheese that had proteolytic activity with a proteolytic index value between 1.14 to 2.14 and had MCA abilities of 1.7 to 2.1 SU/ml. LN-3 and YN-4 were the best isolates because they had a low proteolytic value with a high MCA value. BAL isolates from fresh cheese using pineapple belong to the genus Leuconostoc and Lactobacillus. Yeast isolates from fresh cheese using pineapple and Yeast from pineapple extract is belong to the genus Pichia. This study indicates that LAB and Yeast isolated from fresh cheese and pineapple extract cheese have extracellular proteolytic potential and Milk Clotting Activity (MCA).